Finite element analysis of different ferrule heights of endodontically treated tooth - Kashani, J. (Springer Berlin Heidelberg, 2011)
Objective: To investigate the influence of ferrule height on the crown mechanical resistance and stress distribution through the root and luting cement to explain restoration lose and root fracture pattern. Material and methods: Threedimensional models of an adult maxilla and root of incisor tooth were developed from a Computed Tomography scan images. Periodontal ligament, luting cement, crown and custom post were reconstructed on the computer . A static load of 50N was applied to the crown at 70° to the occlusal plan. Results: Design with no ferrule had the most crown displacement and 2mm ferrule had the least. Also 2mm ferrule design had the lowest root and luting cement stress Conclusion: The study suggests that a ferrule increases mechanical resistance of crown. Furthermore, a ferrule decreases stress in dentin and luting cement; consequently, the fracture and losing restoration risk decline.